Comparative Effectiveness of NHIA Versus Out-of-Pocket Payment Models in Promoting Preventive Healthcare Utilisation in Nigeria - Onuorah, Whitney Adaeze (British Journal of Healthcare and Medical Research, 2025)
Preventive healthcare is essential for reducing disease burden and improving population health outcomes, yet in Nigeria, heavy reliance on individual payments continues to limit means of obtaining this vital care. This study compared the impact of the National Health Insurance Authority (NHIA) model versus OOP payment in promoting the utilization of preventive healthcare in Nigeria using a comparative cross-sectional design, involving selected urban and rural health facilities across Rivers and Ekiti States to capture diverse socioeconomic and infrastructural conditions. A sample of 1,700 adults aged 18 years and above who had accessed preventive services, such as immunisations, screenings, and routine check-ups, within the past year was recruited through a sequential sampling in stages technique. Socio-demographic data, health financing mode, preventive service utilisation, and financial hardship were obtained through structured administered questionnaires and analysed using chi-square tests and logistic regression to control for potential confounders. The results demonstrated significantly higher preventive service utilization among NHIA enrollees compared to OOP payers: immunisations (70% vs. 60%), screenings (66% vs. 56%), and routine check-ups (72% vs. 64%). Additionally, NHIA users reported substantially lower financial hardship (14.2%) compared to OOP payers (42.6%). Logistic regression confirmed that NHIA membership doubled the odds of preventive healthcare utilization after adjusting for education level, geographic location, and healthcare facility adequacy. These findings underscore the success of the NHIA in reducing cost barriers and enhancing access to preventive services. However, persistent rural health infrastructure gaps highlight the need for targeted expansion and upgrading of healthcare facilities in underserved areas. Strengthening rural healthcare systems is recommended to promote equity and maximize the benefits of NHIA coverage.